CAYENNE PEPPER (Capsicum frutescens) ETHANOL EXTRACT EFFECT ON RATS SKIN WOUND HEALING AND MALONDIALDEHYDE (PENGARUH EKSTRAK ETHANOL CABAI RAWIT (Capsicum frutescens) TERHADAP PENYEMBUHAN LUKA DAN MALONDIALDEHYDE KULIT TIKUS) - Dewi Ratih Handayani; Linlin Haeni; Muhammad Rizki Sukmara (Fakultas Kedokteran Gigi Unjani, 2022)
Cayenne pepper (Capsicum frutescent) is often used as spices. Cayenne pepper also has health benefits such as relieving sore muscle, pain, and toothache. Cayenne pepper contains capsaicin, vitamin A, vitamin C, antioxidants. Vitamin A also serves to epithelialize skin, and vitamin C works to stimulate collagen synthesis. This study was conducted to determine the effect of ethanol extract of cayenne pepper on the wound healing time and the levels of malondialdehyde (MDA) on Wistar rats skin. This study used 25 male rats Wistar strain divided into five groups. Chili extract doses used in this study used three-dose concentrations, there were 2%, 1%, and 0.5% for seeking effective dose, which was administered for 14 days. Healing time was measured by observing the downsizing of the diameter of the wound on days 3, 7, and 14 following the phase of wound healing, and MDA levels were measured on day 14. Data were analyzed using the Kruskal-Wallis test followed by the Mann-Whitney test (P<0.05). The results showed that the group who were given extracts of chili with all three concentrations were experiencing delays in wound healing at days fourteen (P=0.01), and MDA levels were higher than the control group. It can be concluded that the extract of chili causes a delay in the healing process because the unmeasured dose of the extract of chili causes the release of free radicals produced by nitric oxide stimulated by capsaicin contained in chili. DOI : 10.54052/jhds.v1n3.p247-258